Implementasi Program Festival Anak Sholeh sebagai Media Pengembangan Karakter Sosial Anak di Desa Negeri Ujung Kahan - Fauziah Nasutio; Adinda Hariana Safitri; Tryana Fauziyah; Sintia Khairiyyahni; Innaya Ramadhini Edith (PADMA, 2025)
The Festival Anak Sholeh program is a religious-based educational activity implemented within the framework of *Community Service (Pengabdian kepada Masyarakat/PEMA), designed as a non-formal learning medium to foster and develop children’s social character through various competitions and interactive activities that encourage active participation. This program was conducted in Negeri Ujung Kahan Village and involved community members, parents, and children as the primary beneficiaries. This study aims to describe the implementation of the *Festival Anak Sholeh as part of the PEMA program and to analyze its role as a medium for developing children’s social character. This study employed a descriptive qualitative approach, with data collected through direct observation of program implementation, in-depth interviews with organizing committee members, parents, and child participants, as well as program documentation. The findings indicate that the implementation of the Festival Anak Sholeh through the PEMA program makes a positive contribution to strengthening children’s social character values, particularly in terms of cooperation, empathy, self-confidence, discipline, and positive social interaction skills. Children were not only trained to develop their religious competencies but were also encouraged to collaborate, respect others, and engage in healthy competition. Furthermore, active community involvement and parental support were identified as key supporting factors in ensuring the effectiveness and sustainability of this community service program. The findings suggest that the Festival Anak Sholeh, as part of a community service initiative, can serve as an effective alternative medium for character education based on religious values in rural communities, while also providing recommendations for the development of similar community service programs oriented toward strengthening children’s social character.